Correction of Intestinal Microbiocenosis Violations in Children with Irritable Bowel Syndrome - T.V. Yaroshevskaya; S.I. Ilchenko; N.B. Sapa; L.N. Kramarenko (Zaslavsky O.Yu., 2016)
The article focuses on an actual problem of treating functional bowel diseases with clinical signs of dysbiosis in children. Objective of the study is assessment of effectiveness of comprehensive therapy with modern symbiotic containing strains Lactobacollus rhamnosus GG and fructooligosaccharides in irritable bowel syndrome children. Materials and methods. The study involves 35 children with irritable bowel syndrome and clinical manifestations of intestinal dysbiosis on the basis of subjective and objective symptoms, character of stool, coprogram and microbiological analysis of feces. Treatment efficacy is assessed taking into account the dynamics of the main symptoms of the disease (impaired stool, flatulence, loss of appetite, abdominal pain), normalization of coprogram indicators, results of the control microbiological analysis of feces. Objectification of the clinical manifestations of the disease is performed at baseline and before discharge of the child from hospital. Results. As a result of the developed schemes of treatment, the abdominal pain syndrome and symptoms of intestinal dyspepsia were quickly stopped. In children with skin manifestation of allergy, their severity has decreased. The clinical manifestations of the digestive disorders syndrome decreased, indicators of coprogram improved. A significant positive dynamics of fecal microbial composition is marked. More than a half of the patients achieve normalization of the quantitative composition of bifid bacteria and lactobacilli; the number of E.coli with altered enzymatic properties reduced, opportunistic and fungal flora was eliminated. The tolerability of prescribed treatment in all patients is good. Conclusions. Correction of intestinal biocenosis occupies an important place in the treatment of irritable bowel syndrome children. The study shows a high efficacy and safety of the combination of Lactobacollus rhamnosus GG and fructooligosaccharides in the comprehensive treatment of the disease that allows to recommend its practical application.